2015
DOI: 10.3389/fgene.2015.00090
|View full text |Cite
|
Sign up to set email alerts
|

Dna Methyltransferase 1 Mutations and Mitochondrial Pathology: Is Mtdna Methylated?

Abstract: Autosomal dominant cerebellar ataxia-deafness and narcolepsy (ADCA-DN) and Hereditary sensory neuropathy with dementia and hearing loss (HSN1E) are two rare, overlapping neurodegenerative syndromes that have been recently linked to allelic dominant pathogenic mutations in the DNMT1 gene, coding for DNA (cytosine-5)-methyltransferase 1 (DNMT1). DNMT1 is the enzyme responsible for maintaining the nuclear genome methylation patterns during the DNA replication and repair, thus regulating gene expression. The mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 160 publications
(269 reference statements)
0
58
0
1
Order By: Relevance
“…DNA methylation is the addition of a methyl group from S-adenosyl-methionine (SAM) to a DNA base usually cytosine (C) or adenine (A) that is catalyzed by specialized enzymes called DNA methyltransferases (DNMTs; reviewed in Maresca et al, 2015). Although cytosine methylation occurs at position C-5 resulting in 5-methylcytosine (5mC), the exocyclic NH 2 group of adenine gets methylated at position 6, which is converted into N6-methyladenine (6mA; Figs.…”
Section: The Enigma Of Mtdna Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA methylation is the addition of a methyl group from S-adenosyl-methionine (SAM) to a DNA base usually cytosine (C) or adenine (A) that is catalyzed by specialized enzymes called DNA methyltransferases (DNMTs; reviewed in Maresca et al, 2015). Although cytosine methylation occurs at position C-5 resulting in 5-methylcytosine (5mC), the exocyclic NH 2 group of adenine gets methylated at position 6, which is converted into N6-methyladenine (6mA; Figs.…”
Section: The Enigma Of Mtdna Methylationmentioning
confidence: 99%
“…Over the last decade, mtDNA methylation has been extensively scrutinized as several studies have identified this modification in cell lines and tissue samples of mouse and human origin, in both normal as well as disease conditions, in young versus aged mice, as well as under various conditions of oxidative stress, nutrition, and environmental exposure (Chestnut et al, 2011;Shock et al, 2011;Dzitoyeva et al, 2012;Bellizzi et al, 2013;Pirola et al, 2013;Wong et al, 2013;Ghosh et al, 2014;Baccarelli and Byun, 2015;Saini et al, 2017). DNA methylation in the mitochondria was first reported almost five decades ago and has been a topic of controversy ever since (reviewed in Maresca et al, 2015;D'Aquila et al, 2017;Mposhi et al, 2017). It is advantageous to measure methylation within the mitochondrial D-loop, because this region harbors the HSP and LSP elements and is easily accessible to proteins during mtDNA replication and transcription where methylation can directly impact these processes .…”
Section: The Enigma Of Mtdna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, there are increasing indication that certain chemicals substances and drugs may regulate gene expression not only during but also after exposure . Epigenetic modification of the mitochondrial genome has been widely debated, but the most recently published data highlight how the methylation of cytosines in the mitochondrial DNA is likely to be much more frequent than previously believed . Particularly relevant is the binding of DNMT1 to the mitochondrial D‐loop control region, the latter driving transcription initiation of both heavy and light strands and playing a role in the regulation of mitochondrial gene expression …”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is a key process for gene expression owing to its effect on DNA replication and repair [5] (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%